The Question of Leadership Styles on Waqf Management in Higher Education in the Age of Digital Era: A Critical Analysis - Nizam, Mohammad Firdaus; Parasuraman, Balakrishnan; Hasan, Hazriah; Ridzwan, Rikinorhakis (INAIFAS Press, 2025)
The role of waqf (Islamic endowment) in supporting higher education institutions has been integral for centuries, providing sustainable funding for various academic and infrastructural needs. In recent times, the dynamics of waqf management are undergoing significant transformations, largely driven by the increasing prominence of digital technology. This paper critically analyses how different leadership styles influence the management of waqf in higher education institutions, particularly in the digital era. It explores the impact of transformational, transactional, and situational leadership styles on the operational efficiency, transparency, and long-term sustainability of waqf funds. The paper also examines the integration of digital tools such as online platforms, blockchain, and big data analytics in enhancing waqf management. By providing a thorough understanding of the intersections between leadership theory and digital transformation, this article offers insights into the critical role of leadership in navigating the challenges and opportunities in the management of waqf in the 21st century.